A Facile Method to Synthesize b-Oriented Silicalite-1 Thin Film - Montree Thongkam; Somsak Woramongkolchai; Sairoong Saowsupa; Pesak Rungrojchaipon (My University, 2022)
Silicalite-1 thin film was prepared with the following batch composition-3TPAOH:25TEOS:1450H
Keywords: Mesoporous Materials and Catalysis